Ligand-induced crystallization control in MAPbBr3 hybrid perovskites for high quality nanostructured films - Heindl, Markus W.; Lichtenegger, Michael; Kodalle, Tim; Liu, Shangpu; Solhtalab, Nasrin; Zerhoch, Jonathan; Shcherbakov, Andrii; Kivala, Milan; Sutter-Fella, Carolin Maria; Urban, Alexander Skyrme; Deschler, Felix (Advanced optical materials, 2025)
Controlling the formation of hybrid perovskite thin films is crucial in obtaining high-performance optoelectronic devices, since factors like morphology and film thickness have a profound impact on a film's functionality. For light-emitting applications grain sizes in the sub-micrometer-range have previously shown enhanced brightness. It is therefore crucial to develop simple, yet reliable methods to produce such films. Here, a solution-based synthesis protocol for the on-substrate formation of MAPbBr3 (MA = methylammonium) nanostructures by adding the bifunctional rac-3-aminobutyric acid to the precursor solution is reported. This synthesis route improves key optical properties such as photoluminescence quantum yields and life times of excited states by inducing a controlled slow-down of the film formation and suppressing agglomeration effects. In situ spectroscopy reveals a delayed and slowed down crystallization process, which achieves synthesis of perovskite structures with much reduced defect densities. Further, aggregation can be controlled by the amount of amino acid added and adjusting the synthesis protocol allows to produce cubic crystallites with targeted size from nanometer to micrometer scales. The nanocrystalline MAPbBr3 samples show enhanced amplified spontaneous emission (ASE) intensities, reduced ASE thresholds and purer ASE signals, compared to pristine films, even under intense optical driving, making them promising structures for lasing applications.
Gesehen am 01.08.2025